Gratitude and forgiveness as predictors of resilience among muslim students in Yogyakarta - Wahyudi, Amien; Wibowo, Mungin Eddy; Mulawarman; Japar, Muhammad; Supriyanto, Agus; Zakaria, Gamal Abdul Nasir (Psikopedagogia, 2025)
This study aims to analyze the effect of gratitude and forgiveness on resilience in Muslim students in Yogyakarta. This study used quantitative research with a correlational approach, data were collected from 392 Muslim students in grades 10 to 12 in Yogyakarta. The scales used in this study were: 1) The Gratitude Questionnaire-Six Item Form (GQ-6); 2) Heartland Forgiveness Scale; and 3) Connor-Davidson Resilience Scale-10 Items. The sample of this study was taken using simple random sampling. Data analyze was conducted using Structural Equation Modelling (SEM). The results showed that both gratitude and forgiveness positively and significantly affected resilience in Muslim students. The path coefficients showed that increased gratitude and forgiveness were correlated with increased resilience. These findings underline the vital role of gratitude and forgiveness as sources of psychological strength in facing challenges and growing resilience among Muslim students. This study contributes to understanding relevant psychological factors in a religious context that can support well-being and resilience in Muslim adolescents. The implications of this study suggest the importance of developing positive strength-based interventions, such as gratitude and forgiveness training, to improve resilience in Muslim students. Islamic-based gratitude counselling is recommended in the future.